2003
DOI: 10.1053/jhep.2003.50180
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Mononuclear Cell Expression of Toll–Like Receptors and Relation to Cytokine Levels in Cirrhosis

Abstract: Activation of macrophages by endotoxin is assumed responsible for increased circulating tumor necrosis factor ␣ (TNF-␣) and soluble TNF receptor (sTNFR) levels in cirrhosis. Relevant to this is expression of Toll-like receptor (TLR) 4 and TLR2, which is critically involved in production of TNF-␣ in response to endotoxin and Gram-positive microbial stimuli, respectively. The first studies on this in cirrhosis are reported here. In 36 cirrhotic patients and 32 controls, we measured (1) circulating endotoxin, TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
133
2
6

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(155 citation statements)
references
References 38 publications
14
133
2
6
Order By: Relevance
“…29,30 However, a recent analysis of the peripheral blood mononuclear cell expression of toll-like receptor 4, responsible for signal transduction leading to the production of tumor necrosis factor-alpha in response to endotoxin, has cast doubt as to the importance of endotoxin as a stimulus for tumor necrosis factor-alpha overproduction in cirrhosis in the clinical setting, irrespective of the etiology of cirrhosis. 24 Whether related to reduction in endotoxemia or other mechanism, the Child-Turcotte-Pugh class improved in nearly 50% of our initially Child-Turcotte-Pugh class B or C synbiotic-treated patients, a proportion significantly higher than that in placebo-treated counterparts (8%). The Child-Turcotte-Pugh class also improved in 29% of patients treated with fermentable fiber alone.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…29,30 However, a recent analysis of the peripheral blood mononuclear cell expression of toll-like receptor 4, responsible for signal transduction leading to the production of tumor necrosis factor-alpha in response to endotoxin, has cast doubt as to the importance of endotoxin as a stimulus for tumor necrosis factor-alpha overproduction in cirrhosis in the clinical setting, irrespective of the etiology of cirrhosis. 24 Whether related to reduction in endotoxemia or other mechanism, the Child-Turcotte-Pugh class improved in nearly 50% of our initially Child-Turcotte-Pugh class B or C synbiotic-treated patients, a proportion significantly higher than that in placebo-treated counterparts (8%). The Child-Turcotte-Pugh class also improved in 29% of patients treated with fermentable fiber alone.…”
Section: Discussionmentioning
confidence: 79%
“…A total of 97 consecutive outpatients with hepatic cirrhosis but no overt HE were screened for MHE, as described below. Cirrhosis was diagnosed histologically in 69 out of 97 (71%) patients and on clinical and radiological grounds 24 in the remaining 28 (29%) patients, in whom biopsy was contraindicated by uncontrolled coagulopathy and/or uncontrolled ascites. Patient characteristics, including the etiology of cirrhosis and Child-Turcotte-Pugh class, 25 are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…154 Patients with cirrhosis have increased serum endotoxin levels, regardless of the etiology of liver disease. 155 Riordan et al 156 reported that in patients with cirrhosis patients the expression of TLR2 is upregulated on peripheral blood mononuclear cells (PBMC) and as a result, recognize Gram-positive bacterial products with a concurrent increase in serum TNF␣. Interestingly, TLR4 expression on PBMC did not significantly differ between controls and paitents with cirrhosis.…”
Section: Prrs and Fibrosismentioning
confidence: 99%